Long-term outcomes of high-dose-rate brachytherapy and external beam radiotherapy without hormone therapy for high-risk localized prostate cancer - Kamitani, Nobuhiko; Watanabe, Kenta; Ikeda, Naoki; Kawata, Yujiro; Tokiya, Ryoji; Hayashi, Takafumi; Miyaji, Yoshiyuki; Tamada, Tsutomu; Katsui, Kuniaki (Japanese journal of radiology, 2024)
Purpose Until March 2018, patients with high-risk localized prostate cancer had been administered high-dose-rate brachytherapy (HDR-BT) combined with external beam radiotherapy (EBRT) without additional hormone therapy (HT) at our institution. In this study, we aimed to evaluate long-term outcomes of this treatment. Materials and methods Patients with prostate cancer who received HDR-BT and EBRT between April 1997 and March 2021 and who were followed up for at least 6 months were included in the study. High-risk groups were classified into five levels according to the National Comprehensive Cancer Network guidelines. The EBRT and HDR-BT doses were 39–45 Gy/13–25 fractions. and 16.5–22 Gy/2–4 fractions, respectively. None of the patients received HT during initial treatment. The Kaplan–Meier method was used to estimate biochemical freedom from failure (bFFF), cause-specific survival (CSS), and overall survival (OS) rates. Biochemical failure was also determined. Results Seventy-two patients were enrolled in the study, with a median follow-up of 91.9 months. The median age and initial prostate-specific antigen (iPSA) level were 71 years and 10.95 ng/mL, respectively. The median biologically effective dose for HDR-BT plus EBRT was 270.3 Gy. The 5- and 7-year bFFF, CSS, and OS rates were 85.2 and 74.2%, 100 and 100%, and 95.7 and 91.9%, respectively. Only the iPSA ≤ 20 group was associated with the higher bFFF rate. The 7-year bFFF rates in the groups with iPSA ≤ 20 and iPSA > 20 were 86.6 and 48.6%, respectively. Conclusion HDR-BT plus EBRT without HT might be an alternative treatment option for patients with high-risk localized prostate cancer and iPSA levels ≤ 20. Further studies are required to validate the efficacy of this treatment strategy.